2011
DOI: 10.1353/hpu.2011.0042
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Health Care among Latinas

Abstract: Despite growing interest in disparities in access to health care, relatively little is known about different facets of care among Latinas, their satisfaction with the care they receive, and the predictors of satisfaction. This study examined whether various health care access and context factors, the quality of the patient-physician interaction, and medical mistrust predict satisfaction with health care among Latina immigrants in New York City. Structured interviews were conducted with 220 Latinas predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
0
35
0
2
Order By: Relevance
“…While some Latino immigrants may be healthier than U.S.-born Latinos and non-Hispanic Whites, this may not be the case in every situation and access to health care has consistently been found to be related to better health outcomes (Abraído-Lanza et al, 2011). Latinos underutilize health care and while underutilization does not necessarily mean poor health, studies have found that as the acculturation process progresses, the health of many Latino immigrants deteriorates (Alderete et al, 2000;Torres, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While some Latino immigrants may be healthier than U.S.-born Latinos and non-Hispanic Whites, this may not be the case in every situation and access to health care has consistently been found to be related to better health outcomes (Abraído-Lanza et al, 2011). Latinos underutilize health care and while underutilization does not necessarily mean poor health, studies have found that as the acculturation process progresses, the health of many Latino immigrants deteriorates (Alderete et al, 2000;Torres, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They found that Hispanic participants were more likely to be dissatisfied with overall healthcare and how their physicians treated them compared with non-Hispanic whites, especially on provider dimensions such as ‘listening carefully’ during a treatment encounter [92]. A recent study found that greater waiting time predicted dissatisfaction with healthcare among Latinas [93]. Chiauzzi and colleagues surveyed healthcare professionals to assess the relationship between provider characteristics and their perception of pain treatment in Hispanic patients.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In these studies, primarily urban and older Latino populations were surveyed. Recent studies have noted a paucity of research on the effects of discriminatory practices and mistrust of providers and the overall health care system among Latinos ,. To date, no studies assessing medical mistrust or perceived discrimination have focused on Latinos living in rural areas or young‐adult Latinos.…”
mentioning
confidence: 99%